Leveraging the power of supercritical fluid chromatography for eco-conscious solutions in pharmaceutical analysis - Krmar Jovana; Svrkota Bojana; Obradović Darija; Vlatković Vladimir; Lazović Saša; Otašević Biljana (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2024)
Initially employed primarily at a preparative scale for enantiomer separation of chiral drug candidates, Supercritical Fluid Chromatography (SFC) is nowadays extensively used in the analytical mode. Recent advances in SFC separation science have emphasized its potential for modern and environmentally friendly pharmaceutical analysis. The aim of this review is to provide a deeper insight into the main fundamental and practical aspects of the SFC technique in order to familiarize readers with its versatile nature and efficiency in creating sustainable chromatographic solutions. All considerations are made primarily in the context of the most widely used mode of operation - achiral SFC. In addition, recent applications of this promising technique are presented at the end of the article to further promote its use in pharmaceutical analytical practice.